2019
DOI: 10.1177/2192568219868472
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Ligamentous Reinforcement of the Upper Instrumented Vertebrae +1 Does Not Decrease Proximal Junctional Kyphosis in Adult Spinal Deformity

Abstract: Study Design: Retrospective cohort study.Objectives: Violation of the posterior soft tissues is believed to contribute to the development of proximal junctional kyphosis (PJK). Biomechanical and clinical studies suggest that augmentation of the posterior ligamentous structures (PLS) may help prevent PJK. The purpose of this study was to evaluate the effect of PLS augmentation on the rate of PJK at 1 year. Methods: A retrospective single-surgeon cohort study was performed of 108 adult spinal deformity patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Surgical nylon tape and semitendinosus allograft have also been used to reinforce the posterior ligamentous structures. 21,22 Similar to our results, Rodriguez-Fontan et al 20 reported an increased latent period to development of PJD of 20 months in an augmented cohort, compared to 7.5 months in the control group (p = 0.018). This study is not without limitations.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical nylon tape and semitendinosus allograft have also been used to reinforce the posterior ligamentous structures. 21,22 Similar to our results, Rodriguez-Fontan et al 20 reported an increased latent period to development of PJD of 20 months in an augmented cohort, compared to 7.5 months in the control group (p = 0.018). This study is not without limitations.…”
Section: Discussionsupporting
confidence: 90%
“…For each study, PJK incidence, Revision Rate for PJK (RR), PJF incidence, reported clinical outcomes and complications were reported in Table 3. Twelve of the included studies reported on PJK incidence, 28-31,33-36,38,39,41,43 10 on revision rate for PJK, 28-31,33,35,36,38,39,41 13 on PJF incidence, 29,32,34-40,42-45 5 on any clinical outcome measure 28,38,40,41,45 and 10 on complications. 28-30,35-39,41,45 Four studies 28-30,37,45 did not elaborate on the type of complications, and could thus not be converted to the classification of Glassman et al 27 If reported, the clinical outcome measures were further elucidated in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the studies compared the intervention to a control group, consisting of patients treated with pedicle screws at the UIV (PS). 28,29,[31][32][33][34][35][36][37][40][41][42][43] The minimal follow-up duration was 12 months. All study characteristics are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies have described various risk factors for PJF after corrective fusion for ASD [10][11][12][13][14][15] . Damage to the Spine Surgery and Related Research J-STAGE Advance Publication (February 10, 2022) Ⓒ The Japanese Society for Spine Surgery and Related Research.…”
Section: Discussionmentioning
confidence: 99%